A comparison of linear and mosaic diagrams for set visualization. (July 2019) - Luz, Saturnino; Masoodian, Masood
Linear diagrams have been shown to compare favourably to better known forms of set visualization, such as Venn and Euler diagrams, in supporting non-interactive assessment of set relationships. Recent studies that compared several variants of linear diagrams have demonstrated that users perform best at tasks involving identification of intersections, disjointness and subsets when using a horizontally drawn linear diagram with thin lines representing sets and employing vertical lines as guide lines. The essential visual task the user needs to perform in order to interpret this kind of diagram is vertical alignment of parallel lines and detection of overlaps. Space-filling mosaic diagrams which support this same visual task have been used in other applications, such as the visualization of schedules of activities, where they have been shown to be superior to linear Gantt charts. In this article, we present an experimental comparison of linear and mosaic diagrams for visualization of set relationships, in terms of accuracy, time-to-answer and subjective ratings of perceived task difficulty. The findings show that the two visualizations are largely similar with respect to these measures, suggesting that the choice of one or the other may be solely guided by other visual design considerations. Mosaic diagrams might be more suitable, for instance, in cases where miniature diagrams representing overviews of relations in different collections of sets are required, such as in small-multiples displays.